2020
DOI: 10.1055/s-0040-1714766
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Color Vision Deficiency among Saudi Dental Students: A Cross-Sectional Study

Abstract: Objective The current research was conducted to evaluate the frequency of color-vision deficiency among dental students of King Khalid University College of Dentistry, Saudi Arabia. Materials and Methods A cross-sectional study was performed among 203 dental students working as interns at male and female dental clinics of King Khalid University College of Dentistry (KKUCOD), Saudi Arabia. The Ishihara color-vision deficiency (CVD) test with 24 plates was used for diagnosis of the problem. Analysis of the data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…The average score for color blindness among the students in the dental prosthesis technology program was statistically significantly higher than that of the students in the faculty of dentistry (p = 0.028). These results are supported by that of a previous study, which reported a higher percentage of color blindness in regions with lower education levels ( 16 ). However, there was no significant difference in the color blindness scores stratified by education year, except for second and fifth years (p = 0.003).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The average score for color blindness among the students in the dental prosthesis technology program was statistically significantly higher than that of the students in the faculty of dentistry (p = 0.028). These results are supported by that of a previous study, which reported a higher percentage of color blindness in regions with lower education levels ( 16 ). However, there was no significant difference in the color blindness scores stratified by education year, except for second and fifth years (p = 0.003).…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies highlighted the need for awareness of dentists and dental technicians of color blindness and its effect on clinical success ( 3 , 15 ). According to previous studies, many dentists have no knowledge of their color vision status, and others who are aware have of no knowledge of the degree of color blindness ( 15 , 16 ). According to the results of the color blindness test in the present study, 13.3% of participants who were unaware that they were color blind had a mild or moderate degree of color blindness.…”
Section: Discussionmentioning
confidence: 99%
“…Barghi et al .,[ 19 ] also, found 7 out of 50 individuals to be color blind in their study while Wasson and Schuman[ 20 ] found 9.3% of the population presenting with color blindness in their study with the males being affected more than females signifying the sex-linked nature of this condition analogous with the findings of the present study. A recent study by Alqahtani et al .,[ 40 ] also, observed a total of 20.19% of male dental students to be affected with red-green color vision deficiency as compared to 1.4% of female students with 44 male and 3 female students identified with red-green color deficiency out of a total sample size of 203 students included in the study. The frequency of total color vision deficiency observed in the study was found to be 3.9%.…”
Section: Discussionmentioning
confidence: 99%
“…Out of a total of 203 patients, 44 males were found to have red-green colour dearth, whereas three females were found to have this disease, indicating that CVD is more frequent in men. The study found a relationship between age and red-green colour vision deficiency, protanopia, and total CVD [14]. Alamoudi et al (2021) conducted a cross-sectional study with 1115 medical students to determine the prevalence and determinants of CVD in medical students.…”
Section: Introductionmentioning
confidence: 99%
“…A population-based research was conducted in Tehran to assess the prevalence of colour impairments in secondaryschool students (ages [12][13][14]. A total of 2,058 students were evaluated using Ishihara pseudoisochromatic colour plates (1,136 males and 922 females).…”
Section: Introductionmentioning
confidence: 99%